Factors Affecting the Migration Decision of Tsunami Survivors from the Relocation Area - Saiful Mahdi; Nany Salwa; Cut Mardiana (Proceedings of AICS - Social Sciences, 2017)
The government has undertaken a relocation program to address the housing problems caused by the earthquake and tsunami of December 26, 2004 in Aceh. However, the relocation of tsunami survivors also caused other impacts after the relocation was carried out. If the relocation site is not as desirable, it can cause tsunami survivors to decide to out-migrate the relocation area. This study was conducted to determine factors that significantly affect the decision of migration of tsunami survivors from the relocation area. This research is expected to provide information on post-disaster relocation for consideration in making relocation policy in the future. We use classification tree, which is part of the CART (Classification and Regression Trees) method. The data used is from The Aftermaid of Aid (AoA) survey conducted by International Center for Aceh and Indian Ocean Studies (ICAIOS) and Earth Observatory of Singapore (EOS) during 2014-2015. The results of the research indicate the factors that significantly affect the migration decision of tsunami survivors from a relocation area are gender, age, and job before relocation, total assets, and the distance of relocation house to central market, house modification, and concerns about possible of future tsunami. Most affecting factor of migration decision, however, is the distance of relocation house to the central market, confirming the impact of sosio-economic factor of post-disaster relocation. The optimal classification tree obtained has a classification accuracy rate of 85, 64%.